Genetic Determinants Of Helicobacter Pylori Virulence And Gastric Cancer Suspectibility: A Systematic Review - Muhammad Hisyam Dzaki Alimuddin; Felicia Virginia Thios; Nabila Hana Zahirah Amri (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Gastric cancer (GC) remains a leading cause of cancer mortality, with Helicobacter pylori (H. pylori) infection recognized as a major carcinogen. Virulence genes such as cagA, cagE, and vacA, along with specific cag pathogenicity island (PAI) polymorphisms, are implicated in gastric mucosal injury and malignant transformation. This systematic review aimed to identify H. pylori genotypes associated with increased GC risk. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted in PubMed, ProQuest, and ScienceDirect. Eligible studies included case-control or cross-sectional designs assessing H. pylori virulence genotypes among GC and non-GC patients. Data were extracted and summarized descriptively based on odds ratios (ORs) and genotype distributions. Results and Discussion: From 4,359 screened records, five studies met inclusion criteria. The vacA c1 allele was linked to a higher GC risk (OR = 3.14, 95% CI 1.08–9.09), and cagA+cagE co-expression increased susceptibility (OR = 0.46, 95% CI 0.24–0.86). In Japan, East-Asian cagA with vacA s1m1 showed the strongest association (OR = 6.68, 95% CI 1.73–25.8), while multiple cagA EPIYA-C motifs in Brazilian isolates tripled GC risk (OR = 3.08, 95% CI 1.74–5.45). Latin American data identified cagA and cagC variants significantly enriched in GC isolates. These findings indicate that cagA and vacA synergistically drive epithelial disruption and inflammation, underpinning their oncogenic potential. Conclusion: CagA, vacA, and cagE genotypes represent key H. pylori virulence predictors of GC. Integrating genotypic profiling into clinical risk assessment could improve early detection and targeted prevention strategies.